The influence of rapid growth on sodium salicylate pharmacokinetics in male turkeys. Issue 1 (29th June 2017) - Poźniak, B.; Motykiewicz‐Pers, K.; Grabowski, T.; Świtała, M.
Abstract : The aim of this study was to assess the influence of growth on the pharmacokinetics of sodium salicylate (SS) in male turkeys. SS was administered intravenously at a dose of 50 mg/kg. Plasma drug concentrations were assessed by high‐performance liquid chromatography, and pharmacokinetic parameters were calculated by noncompartmental analysis. As the age increased from 6 to 13 weeks (body weight increase from 2.35 to 9.43 kg), median body clearance decreased from 1.34 to 0.87 ml/min/kg. This caused a significant increase in the median mean residence time from 3.42 to 4.44 hr. Elimination phase proved to be biphasic and two elimination half‐lives ( T 1/2el ) were distinguished. Whereas T 1/2el1 was found to increase with age by 128%, T 1/2el2 represented a later but faster and less age‐dependent phase of elimination (increase by 56% in the respective groups). Volume of distribution decreased with age. These effects may lead to different therapeutic response to SS in turkeys of different age and body weights.